2016
DOI: 10.1167/iovs.16-20128
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Choroidal Thickness in Former Preterm and Full-Term Infants Aged From 4 to 10 Years

Abstract: Our results indicate that prematurity itself does not affect choroidal thickness in the peripapillary region. Only infants born SGA revealed peripapillary choroidal thinning compared with AGA infants. Our data indicate that fetal growth restriction leads to choroidal long-term alterations in the peripapillary region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
0
18
0
3
Order By: Relevance
“…Furthermore, CCT is negatively associated with body height [46] and positively associated with body weight in men and with body mass index in all subjects [40]. These parameters are known to be-at least partially-influenced by LBW and LBW may to some extent explain those associations with altered corneal thickness [5,7,9] and ocular geometry [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CCT is negatively associated with body height [46] and positively associated with body weight in men and with body mass index in all subjects [40]. These parameters are known to be-at least partially-influenced by LBW and LBW may to some extent explain those associations with altered corneal thickness [5,7,9] and ocular geometry [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Several efforts have been made to overcome the limitations of subfoveal CT measurements in isolation. In some studies, CT measurements at locations other than the macula or subfoveal CT have been attempted in various diseases ( 23 , 79 , 82 , 89 , 104 , 108 ). In others, CT was measured both at the macula and outside the macular region ( 26 , 32 , 77 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…Children have also been subjected to peripapillary CT measurements. Fieß et al ( 108 ) reported that premature birth itself does not affect peripapillary CT, however they found that infants born small for their gestational age had peripapillary choroidal thinning when compared to those infants born at the appropriate gestational age. Li et al ( 96 ) measured macular and parapapillary CT in children with diabetes and reported that inferior and nasal parapapillary CT were increased in children with type 1 diabetes and without retinopathy or visual impairment as compared to healthy controls.…”
Section: Choroidal Thickness Measurement Beyond the Maculamentioning
confidence: 98%
“…The theory presented by Barker 6,23 first described low birth weight as an indicator of fetal origins for adult cardiovascular disease. Low birth weight leads to multiple morphologic changes of the eye during infancy and childhood, 8,[24][25][26] which may conceivably predispose these individuals to AMD. Our study observed a higher prevalence of AMD in low birth weight compared to normal birth weight individuals.…”
Section: Discussionmentioning
confidence: 99%